157k views
5 votes
Does Anyone know this?

Does Anyone know this?-example-1

1 Answer

3 votes

Answer:

∠AEC = 139°

Explanation:

Since EC bisects ∠BED then ∠BEC = ∠CED = 4x + 1

∠AED = ∠AEB + ∠BEC + ∠CED = 180 ← straight angle

Substitute values into the equation

11x - 12 + 4x + 1 + 4x + 1 = 180, that is

19x - 10 = 180 ( add 10 to both sides )

19x = 190 ( divide both sides by 19 )

x = 10

Hence

∠AEC = ∠AEB + ∠BEC = 11x - 12 + 4x + 1 = 15x - 11, hence

∠AEC = (15 × 10) - 11 = 150 - 11 = 139°

User Ventik
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.